Feminist and human rights struggles in Peru: decolonizing transitional justice - Bueno-Hansen, Pascha (Dissident feminisms, 2015)
Parallel tracks and fraught encounters : the human rights and feminist movements (and campesina protagonism) in peru -- Gender implementation in the peruvian truth and reconciliation commission -- National reconciliation through public hearings : representative repertoire, choreography, and politics of reception -- Sexual violence beyond consent and coercion -- Finding each other's hearts : weaving interculturality into gender and human rights